Radiation dose escalation with modified fractionation schedules for locally advanced NSCLC: A systematic review. Issue 6 (22nd April 2020) - Zehentmayr, Franz; Grambozov, Brane; Kaiser, Julia; Fastner, Gerd; Sedlmayer, Felix
Abstract: Concomitant chemo‐radiotherapy (cCRT) with 60 Gy in 30 fractions is the standard of care for stage 111 non‐small cell lung cancer (NSCLC). With a median overall survival of 28.7 months at best and maximum locoregional control rates of 70% at two years, the prognosis for these patients is still dismal. This systematic review summarizes data on dose escalation by alternative fractionation, which has been explored as a primary strategy to improve both local control and overall survival over the past three decades. A Pubmed literature search was performed according to the PRISMA guidelines. Because of the large variety of radiation regimens total doses were converted to EQD2, T . Only studies using an EQD2, T of at least 49.5 Gy, which corresponds to the conventional 60 Gy in six weeks, were included. In a total of 3256 patients, the median OS was 17 months (range 7.4–30 months). While OS was better for patients treated after the year 2000 ( P = 0.003) or with a mandatory 18 F‐FDG‐PET‐CT in the diagnostic work‐up ( P = 0.001), treatment sequence did not make a difference ( P = 0.106). The most commonly reported toxicity was acute esophagitis (AE) with a median rate of 24% (range 0%–84%). AE increased at a rate of 0.5% per Gy increment in EQD2, T ( P = 0.016). Dose escalation above the conventional 60 Gy using modified radiation fractionation schedules and shortened OTT yield similar mOS and LRC regardless of treatment sequence with a significant EQD2, T dependent increase in AE. Key points: Significant findings Modified radiation dose escalation sequentially combined with chemotherapy yields similar outcome as concomitant treatment. OS is better with the mandatory inclusion of FDG‐PET‐CT in the diagnostic work‐up. The risk of acute esophagitis increases with higher EQD2, T . What this study adds Chemo‐radiotherapy (CRT) with modified dose escalation regimens yields OS and LC rates in the range of standard therapy regardless of treatment sequence. This broadens the database of curative options in patients who are not eligible concomitant CRT.